International Trends and Developments in the Ethnography of Education - Beach, Dennis (Acta Paedagogica Vilnensia, 2017)
The history of ethnography in social science in Europe dates back to before a 1907 debate in Paris involving leading social scientists, such as Emile Durkheim and René Worms. Worms was one of the first speakers. His account of ethnography was of a descriptive, a-historical method for researching the so-called “primitive societies.” Durkheim, who spoke after Worms, disagreed. Ethnography, he suggested, can provide a basis for both analyzing and synthesizing the understandings of past cultures in relation to the present and, as all human societies have their versijon of civilization, ethnography can be applicable to any of them, he added. Ethnologists and historians in Germany had made this point in fact over a hundred years earlier and most ethnographers have taken this position since Durkheim’s proposition. Martyn Hammersley is amongst them. In his opening article in the inaugural number of the Journal of Ethnography and Education in 2006, he described how ethnography has been used for over 100 years in social science, as a method to investigate cultural meanings and practices influenced by both modern and postmodern epistemologies and a diverse range of theories and methodologies. This article addresses the development sketched by Hammersley and other writers in the field.
Keywords: ethnography; history; anthropology; education research